Metabolic engineering of Corynebacterium glutamicum for the production of 3-hydroxypropionic acid from glucose and xylose - Chen, Zhen; Huang, Jinhai; Wu, Yao; Wu, Wenjun; Zhang, Ye; Liu, Dehua (Metabolic engineering, 2017)
3-Hydroxypropionic acid (3-HP) is a promising platform chemical which can be used for the production of various value-added chemicals. In this study,Corynebacterium glutamicum was metabolically engineered to efficiently produce 3-HP from glucose and xylose via the glycerol pathway. A functional 3-HP synthesis pathway was engineered through a combination of genes involved in glycerol synthesis (fusion of gpd and gpp from Saccharomyces cerevisiae) and 3-HP production (pduCDEGH from Klebsiella pneumoniae and aldehyde dehydrogenases from various resources). High 3-HP yield was achieved by screening of active aldehyde dehydrogenases and by minimizing byproduct synthesis (gapAA1GΔldhAΔpta-ackAΔpoxBΔglpK). Substitution of phosphoenolpyruvate-dependent glucose uptake system (PTS) by inositol permeases (iolT1) and glucokinase (glk) further increased 3-HP production to 38.6g/L, with the yield of 0.48g/g glucose. To broaden its substrate spectrum, the engineered strain was modified to incorporate the pentose transport gene araE and xylose catabolic gene xylAB, allowing for the simultaneous utilization of glucose and xylose. Combination of these genetic manipulations resulted in an engineered C. glutamicum strain capable of producing 62.6g/L 3-HP at a yield of 0.51g/g glucose in fed-batch fermentation. To the best of our knowledge, this is the highest titer and yield of 3-HP from sugar. This is also the first report for the production of 3-HP from xylose, opening the way toward 3-HP production from abundant lignocellulosic feedstocks. •Corynebacterium glutamicum was engineered for the first time to produce 3-hydroxypropionic acid (3-HP) from glucose via glycerol pathway.•62.6g/L of 3-HP was produced from glucose at a yield of 0.51g/g, the highest titer and yield of 3-HP from sugar reported to date.•Downregulation of glyceraldehyde 3-phosphate dehydrogenase and employment of the non-PTS glucose-uptake system are important for increasing the yield of 3-HP.•3-HP overproduction by simultaneous utilization of glucose and xylose was achieved.